2020
DOI: 10.3389/fpsyt.2020.00069
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Child Maltreatment, Autonomic Regulation, and Adverse Cardiovascular Outcome in an Urban Population: The HELIUS Study

Abstract: The cumulative exposure to child maltreatment was negatively associated with BRS and HRV, but the association was no longer significant after correction for socioeconomic and demographic covariates. Conclusion: In a large, multi-ethnic urban-population cohort study we observed a positive association between number of endorsed child maltreatment types and selfreported aCVO but not autonomic regulation, over and above the effect of relevant demographic, health, and psychological factors. Future studies should ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 63 publications
1
18
0
Order By: Relevance
“…A large population-based multi-ethnic urban cohort study tested whether child maltreatment, such as emotional neglect, emotional abuse, physical abuse, and sexual abuse, was associated with a higher risk of self-reported history of CVD. The study confirmed that child maltreatment is significantly associated with a higher risk of CVD later in life, and that this association remained significant after adjusting for potentially relevant covariates [24].…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…A large population-based multi-ethnic urban cohort study tested whether child maltreatment, such as emotional neglect, emotional abuse, physical abuse, and sexual abuse, was associated with a higher risk of self-reported history of CVD. The study confirmed that child maltreatment is significantly associated with a higher risk of CVD later in life, and that this association remained significant after adjusting for potentially relevant covariates [24].…”
Section: Introductionsupporting
confidence: 72%
“…Specifically, experiencing emotional neglect, emotional abuse, physical abuse, starting from early childhood, seemed to be associated with the presence of a CVD. Moreover, the amount and the impact of emotional abuse experienced during childhood and adolescence were higher in the patients with the CVDs compared to the control group, further supporting the role of traumatic events in the development of a CVD [ 24 ].…”
Section: Discussionmentioning
confidence: 89%
“…Evidence from epigenetic studies suggests that the experience of early maltreatment “gets under the skin” through processes such as DNA methylation (Cecil, Zhang, & Nolte, 2020). There is also growing evidence that maltreatment results in long‐term harm to physical systems, such as the cardiovascular system (Bakema et al, 2020) and the immune system (do Prado, Grassi‐Oliveira, Daruy‐Filho, Wieck, & Bauer, 2017). There is no doubt that maltreatment can result in severe and lasting harm to children.…”
mentioning
confidence: 99%
“…Second, the psychological and physiological impacts of certain forms of childhood trauma do not necessarily have a deterministic effect on future elevated disease risk or adversely affect the stress physiological pathways understood to underlie these long-term effects. For example, previously published studies have found null associations between early life stress and adult stress physiology outcomes, including autonomic regulation [ 40 , 41 ] and hypothalamic-pituitary-adrenal axis function [ 41 , 42 ]. Given the increased prevalence and burden of both ACEs and CVDs in low- and middle-income contexts, further research studies from these settings are needed to elucidate the possible long-term effects of ACEs on adult CVD risk.…”
Section: Discussionmentioning
confidence: 99%